THE INFLUENCE OF ORGANIZATIONAL JUSTICE AND TRANSFORMATIONAL LEADERSHIP THROUGH JOB SATISFACTION ON ORGANIZATIONAL COMMITMENT - Rara Cahya Andini; Trias Setiawati Setiawati (MANAJEMEN DEWANTARA, 2020)
The purpose of this study was to determine the mediation of job satisfaction in a relationship between organizational justice and transformational leadership on organizational commitment.Â  A total of 170 participants who are working in BIAS Yogyakarta have joined this research. Method of collecting data using a questionnaire by conducting regression with analyzing use t-test, F-test, Path analysis with Sobel test. The result of this study found that organizational justice has positive and significant impact on job satisfaction, transformational leadership have positive and significant impact on job satisfaction, organizational justice has negative impact on organizational commitment, transformational leadership have positive and significant impact on organizational commitment, job satisfaction has negative impact on organizational commitment, job satisfaction have mediating effect between organizational justice and organizational commitment, and job satisfaction have mediating effect between transformational leadership and organizational commitment.Kata Kunci: organizational justice, transformational leadership, job satisfaction, organizational commitmentÂ